Active surveillance for PTMC warranted for the UK population?. (13th October 2022) - Maniam, Pavithran; Harding, Noah; Li, Lucy; Adamson, Richard; Hay, Ashley; Nixon, Ian
Abstract: Background: The incidence of thyroid cancer is increasing globally due to the increase in detection of subclinical, low volume papillary thyroid microcarcinomas (PTMC) (<1 cm). Several international groups have recommended an active surveillance approach for this low‐risk disease. In contrast to many other countries, the United Kingdom's (UK's) approach to thyroid nodules is to avoid detection of incidental lesions where appropriate. Objective: This study aims to establish the proportion of patients with thyroid cancer in the UK that would benefit from active surveillance. Design, participants, and outcome measures: Individuals with PTMC in NHS Lothian from 2009–2020 were reviewed from a local thyroid cancer database. The mode of detection of PTMC and proportion of patients who might benefit from active surveillance were established. Results: From 651 individuals with differentiated thyroid cancer managed over 12‐year period, 185 individuals with PTMC were identified (28.4%). The majority of PTMC 151/185 (81.6%) were either diagnosed post‐operatively following thyroidectomy for benign disease or with nodal disease. Only 24 individuals with PTMC were identified following palpable thyroid nodule, incidental finding on imaging, and surveillance screening. Therefore, when the indication for surgery was considered, only 24/651 (3.7%) patients were identified pre‐operatively and would, therefore, be realistic candidates for active surveillance. Conclusion: Less than 4% of patients with thyroid cancer in the UK would be appropriate for active surveillance. Rather than developing programmes to deal with this minority of patients, focus should be maintained on minimising detection of these low‐risk cases.